Características ópticas e morfológicas de nanoestruturas de ouro - Pereira, Francisco Claudece; Zanoni, Maria Valnice Boldrin [UNESP]; Moretto, Ligia Maria; Ugo, Paolo (My University, 2007)
The present study describes a new procedure to obtain gold nanoparticles, directly in the pores of polycarbonate membranes commonly used in ultrafiltration. The dimensions of the particles may be controlled through the reduction time of the ions in the channels of the harbor matrix. The dissolution of the metallized polymer enables an investigation of the optical and morphologic properties of these elements.
Optical and morphological characteristics of gold nanostructures
Keywords: Colloidal gold; Nanoparticles; Polycarbonate membrane